Lymphocytic choriomeningitis virus (LCMV) infection of macaques: A model for Lassa fever - Zapata, Juan C.; Pauza, C. David; Djavani, Mahmoud M.; Rodas, Juan D.; Moshkoff, Dmitry; Bryant, Joseph; Ateh, Eugene; Garcia, Cybele; Lukashevich, Igor S.; Salvato, Maria S. (Antiviral research, 2011)
► History of LCMV infections of primates (from mice to monkeys and man). ► Comparison of outcomes in murine and primate infections. ► Description of findings from LCMV-infected rhesus macaques. ► Utility of the model for testing host-response antivirals over virus-specific antivirals. Arenaviruses such as Lassa fever virus (LASV) and lymphocytic choriomeningitis virus (LCMV) are benign in their natural reservoir hosts, and can occasionally cause severe viral hemorrhagic fever (VHF) in non-human primates and in human beings. LCMV is considerably more benign for human beings than Lassa virus, however certain strains, like the LCMV-WE strain, can cause severe disease when the virus is delivered as a high-dose inoculum. Here we describe a rhesus macaque model for Lassa fever that employs a virulent strain of LCMV. Since LASV must be studied within Biosafety Level-4 (BSL-4) facilities, the LCMV-infected macaque model has the advantage that it can be used at BSL-3. LCMV-induced disease is rarely as severe as other VHF, but it is similar in cases where vascular leakage leads to lethal systemic failure. The LCMV-infected macaque has been valuable for describing the course of disease with differing viral strains, doses and routes of infection. By monitoring system-wide changes in physiology and gene expression in a controlled experimental setting, it is possible to identify events that are pathognomonic for developing VHF and potential treatment targets.